Very Weak Solutions of p-Laplacian Type Equations with VMO Coefficients (Journal of Partial Differential Equations, 2001)
In this note we obtain a new a priori estimate for the very weak solutions of p-Laplacian type equations with VMO coefficients when p is close to 2, and then prove that the very weak solutions of such equations are the usual weak solutions. Our approath is based on the Hodge decomposition and the L^p-estimate for the corresponding linear equations. And this also provides a simpler proof for the results in [1].